Build Social Networks-Based Audio Engineering (Design And Build An Audio-Based Social Network) - Ervan Yudi Widyarto; Chairul Anwar (Eduvest - Journal of Universal Studies, 2022)
Social networks or social media is structure social that builds from node to node which generally is individual or organization. That will bundle with one or more type relation specific like score, vision, idea, friends and posterity and others. Analysis social network look at social connection like node or tie This time is so many social networks that already operation but all of them still using based on text for send message, comment, and email so it will the problem that mostly happen by smart phone user is they have difficulties for typing and for PC user occasionally having mistake because miss understanding meaning from sender.